Comparation Protection Level of Newcastle Disease in Broiler - Sarwo Edy Wibowo; Widya Asmara; Michael Haryadi Wibowo; Bambang Sutrisno (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2013)
Newcastle Disease (ND) is both respiratory and digestive diseases in poultry caused by avian paramyxovirus type 1 (APMV-1). Field data showedthat there were still many cases of Newcastle Disease faced by farmers despite of vaccination programs had been doneroutinely. The aim of this research is to find out the effectiveness of some routine ND vaccination program in broiler chiken challengedeither with viscerotropic velogenic Newcastle Disease (VVND) virus or virulent ND virus from field isolates. One hundred broiler chickens were divided into 4 groups of 25 each. In theGroup I,vaccination was carried out at day 1 with combination of ND-IB live vaccineand ND killed vaccine, and booster at day 18 with live ND vaccine, in the Group II, chickens were vaccinated with live ND-IB vaccine at day 1 and day 18 and in the Group III, chickens were vaccinated with live ND-IB vaccine at day 1 and vaccinated with ND live vaccine at day 18. Challenge test performed in twenty broiler chickens of each group with virulent ND that has chicken lethal dose fifty (CLD50) 4,8. Virus preparation 26 and then diluted to 10-4, to obtain dilution 10000. Twenty chicken from each group were then given 0.5 cc dilution of 6 HA virulent virus at 28 days of old. Six challenged chicken from group I showed ND clinical symptom and were eventually death. This mean that the vaccine program provided 70% protection. Whereas all challenged chicken from the Groups II and III were sick, then died meaning that these vaccination programs did not give any protection at all. Bsed on the present study, it is concluded that the administration of ND live vaccine priming along with ND killed vaccine is needed to improve the protection against velogenic NDV.